2007
DOI: 10.1103/physreve.75.051504
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies of a phenomenological model for elongated virus capsid formation

Abstract: We study a phenomenological model in which the simulated packing of hard, attractive spheres on a prolate spheroid surface with convexity constraints produces structures identical to those of prolate virus capsid structures. Our simulation approach combines the traditional Monte Carlo method with a modified method of random sampling on an ellipsoidal surface and a convex hull searching algorithm. Using this approach we identify the minimum physical requirements for nonicosahedral, elongated virus capsids, such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 30 publications
7
49
0
Order By: Relevance
“…Apart from the computationally involved and physically hardly rewarding fullatom approach 13 , the goal of most of the work done so far on this matter is a good coarse-grained model of such PES. The simplest models represent the capsomers as isotropic bodies, but they require additional geometrical constraints such as a template of the virus capsid [14][15][16][17][18][19] . In other more complex models each capsomer is represented as a discrete set of either isotropic 17,[20][21][22][23][24] or anisotropic interaction centres [25][26][27] , or as a continuous body of interaction points plus some extra discrete centres 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the computationally involved and physically hardly rewarding fullatom approach 13 , the goal of most of the work done so far on this matter is a good coarse-grained model of such PES. The simplest models represent the capsomers as isotropic bodies, but they require additional geometrical constraints such as a template of the virus capsid [14][15][16][17][18][19] . In other more complex models each capsomer is represented as a discrete set of either isotropic 17,[20][21][22][23][24] or anisotropic interaction centres [25][26][27] , or as a continuous body of interaction points plus some extra discrete centres 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen and Glotzer studied the optimal packing of identical hard spheres with square-well interactions on a prolate spheroid surface with convexity constraints (28). They showed that the elongated optimal structures, composed of 15, 17, 18, and 42 identical units, resemble the hypothetical structures of aberrant FHV (24) and of native ϕ29 (19), even though these viruses have two types of morphological units rather than one.…”
mentioning
confidence: 99%
“…Prior theoretical and computational studies of multicomponent assembly have examined the equilibrium behavior of polyelectrolyte encapsidation [59][60][61][62][63] and the equilibrium configurations of colloids confined to convex surfaces [27,64]. A qualitative kinetic model has been proposed to explain the formation of icosahedral symmetry in encapsidated RNA [65] and Hu and Shklovskii [66] considered a model in which capsid proteins nonspecifically bind to single-stranded RNA and slide on it towards an assembling capsid at one end, which increases the rate of assembly.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17]) and insightful theoretical works (e.g. [18][19][20][21][22][23][24][25][26][27][28][29][30][31]). The in vivo replication of many viruses, however, involves simultaneous assembly and encapsidation of the viral genome [32].…”
Section: Introductionmentioning
confidence: 99%